Shedding light on bioluminescence regulation in Vibrio fischeri - Miyashiro, Tim (2012)
The bioluminescence emitted by the marine bacterium Vibrio fischeri is a particularly striking result of individual microbial cells coordinating a group behavior. The genes responsible for light production are principally regulated by the LuxR-LuxI quorum-sensing system. In addition to LuxR-LuxI, numerous other genetic elements and environmental conditions control bioluminescence production. Efforts to mathematically model the LuxR-LuxI system are providing insight into the dynamics of this autoinduction behavior. The Hawaiian squid Euprymna scolopes forms a natural symbiosis with V. fischeri, and utilizes the symbiont-derived bioluminescence for certain nocturnal behaviors, such as counterillumination. Recent work suggests that the tissue with which V. fischeri associates not only can detect bioluminescence but may also use this light to monitor the V. fischeri population.